2009
DOI: 10.1016/j.jhydrol.2009.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration from a Mediterranean evergreen oak savannah: The role of trees and pasture

Abstract: Mediterranean evergreen oak woodlands of southern Portugal (montados) are savannah-type ecosystems with a widely sparse tree cover, over extensive grassland. Therefore, ecosystem water fluxes derive from two quite differentiated sources: the trees and the pasture. Partitioning of fluxes according to these different sources is necessary to quantify overall ecosystem water losses as well as to improve knowledge on its functional behaviour. In southern Iberia, these woodlands are subjected to recurrent droughts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 55 publications
(84 reference statements)
7
59
0
2
Order By: Relevance
“…In the CA location, the presence of graywackes (a hard bed rock) and slates probably limits the development and number of deep tap roots that can access the local groundwater reservoir. Paço et al (2009), also working in a dehesa, found a high resilience of Holm Oaks to drought. The cited authors found that the decline in transpiration during very dry years (2004 and 2005 in their study area) was only 16%, much smaller than the decline in annual rainfall.…”
Section: Discussionmentioning
confidence: 98%
“…In the CA location, the presence of graywackes (a hard bed rock) and slates probably limits the development and number of deep tap roots that can access the local groundwater reservoir. Paço et al (2009), also working in a dehesa, found a high resilience of Holm Oaks to drought. The cited authors found that the decline in transpiration during very dry years (2004 and 2005 in their study area) was only 16%, much smaller than the decline in annual rainfall.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, water uptake from deep subsoil has been shown to be critical in meeting atmospheric transpiration demand in water-limited environments (e.g. Jipp et al, 1998;Oliveira et al, 2005), especially where roots can reach shallow groundwater (Zhang et al, 1999;Zencich et al, 2002;Lamontagne et al, 2005;Cleverly et al, 2006;Gazal et al, 2006;Paço et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…That increase took place despite lowering of water table, which confirmed that water table depth had no or negligible influence on T g and that the trees are adapted to tap water from any accessible reservoir in order to satisfy the transpiration requirements. These results are in agreement with several other studies such as David et al (2004);Paço et al (2009);Miller et al (2010) that independently found that oak trees in savanna environment could compensate low soil moisture in dry season by taping groundwater at depth of 8 and 13 m. These authors also found that groundwater uptake was thermodynamically favorable over soil water uptake during dry seasons and that such behavior was compatible with the tree physiology. However, as the transpiration rates were below the atmospheric water demand, groundwater uptake constitutes a tree strategy to subsist during dry season and not a mechanism for continued plant growth.…”
Section: Groundwater Transpiration Functionsupporting
confidence: 92%